Beyond the Classroom Through the Paperless Mode - Baby, K. Thomas; Saeed, Muhammad Amir (International Journal of Linguistics, Literature and Translation, 2020)
The development of technology in the modern world has necessitated the evolution of paperless classrooms. However, the transformation of educational technology and educational resources has not been able to keep pace with the growth of digital technology that we witnessed in the employment sector. Even today, textbooks and notebooks are widely used as primary teaching and learning tools in many universities across the Arabian Peninsula. The academic community has been making conscious moves to migrate into paperless classrooms in many higher education institutions across Oman through the increased application of computer and internet technology for instructional purposes. The digital mode of instruction can be considered as a conscious attempt to prepare and equip the learners for the paperless digital era. The theory and practice of paperless classrooms are analyzed critically in the first part. The second part of the paper is more specifically an observational analysis of the undergraduate students of Dhofar University and their engagement with digital devices in the classroom. The present educational scenario in the Arabian Peninsula in general and Dhofar University in particular demand a serious study of the concept of paperless classrooms to equip the students to look beyond the classrooms into the challenging avenues of employment opportunities. This study is an attempt to critically examine the paperless mode of education in Oman with special reference to the learners of English at Dhofar University, Salalah, Oman. The study finds that paperless classrooms are more dynamic, engaging and productive that will enable learners not only to develop autonomous learning, data collection and analysis, collaboration and teamwork in the classroom but also delimiting the geographical and time restrictions. Paperless classrooms equip learners with the technological skills that are in demand in the 21st-century for employability, e-business and eCommerce.